Pole piece and battery

By providing an active material layer, an inorganic particle layer and a groove on the electrode sheet of the lithium-ion battery, the problem of difficulty in improving energy density and fast charging performance in the prior art is solved, and a battery with high energy density and fast charging performance is realized.

CN222637302UActive Publication Date: 2025-03-18JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420894055.0
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-04-26
Publication Date
2025-03-18
Estimated Expiration
2034-04-26

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the energy density and fast charging performance of lithium-ion batteries. Molten foreign matter is prone to appear during laser etching, which affects battery capacity and safety.

Method used

The active material layer and the inorganic particle layer are provided on the current collector, and grooves are provided on the inorganic particle layer and the active material layer. The formed pole sheet can improve the energy density and fast charging performance of the battery.

Benefits of technology

The tortuosity of lithium ion transmission is reduced by setting the grooves, and the charging performance of the battery is improved; the binding force between the inorganic particle layer and the active material layer increases the energy density of the battery and increases the safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222637302U_ABST
    Figure CN222637302U_ABST
Patent Text Reader

Abstract

The utility model relates to the technical field of secondary batteries, and provides a pole piece and a battery. The pole piece comprises a current collector, an active substance layer arranged on the surface of the current collector and an inorganic particle layer arranged on the surface, far away from the current collector, of the active substance layer, wherein the particle size of inorganic particles in the inorganic particle layer is 10-50 nm; the inorganic particle layer and the active material layer are provided with grooves. The battery formed by the pole piece disclosed by the utility model is high in energy density, high in capacity retention ratio and high in charging speed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of secondary batteries, in particular to a pole piece and a battery. Background Art

[0002] In the field of power batteries, energy density and charging rate are important indicators for evaluating battery performance. Generally speaking, the greater the battery energy density, the more conducive it is to improving the range of new energy vehicles. The greater the battery charging rate, the more conducive it is to improving the battery's fast charging capability. Therefore, it is particularly important to improve the battery's energy density and fast charging performance. However, the current method to increase battery energy density is usually to increase the coating weight of the positive and negative electrodes, but the increase in the coating weight of the positive and negative electrodes will reduce the battery's fast charging performance.

[0003] Although laser etching of the thick-coated electrode surface is beneficial to enhancing the fast charging capability of lithium-ion batteries, molten beads often appear during the laser etching process. The molten beads are easily sputtered to both sides of the etching point, causing the electrode material area to be damaged by the high-temperature molten beads, thereby affecting the capacity of the lithium-ion battery or causing lithium precipitation, posing a safety hazard.

[0004] Therefore, there is an urgent need to develop an electrode that can simultaneously improve battery energy density and fast charging performance. Utility Model Content

[0005] The purpose of the utility model is to overcome the above problems existing in the prior art and provide a pole piece and a battery. The pole piece of the utility model is obtained by arranging an active material layer and an inorganic particle layer on a current collector, and arranging grooves on the inorganic particle layer and the active material layer. The battery composed of the pole piece has a high energy density, a high capacity retention rate, and a fast charging speed.

[0006] In order to achieve the above-mentioned purpose, the first aspect of the utility model provides a pole piece, which includes: a current collector, an active material layer arranged on the surface of the current collector, and an inorganic particle layer arranged on the surface of the active material layer away from the current collector, the particle size of the inorganic particles in the inorganic particle layer is 10nm-50nm; grooves are arranged on the inorganic particle layer and the active material layer.

[0007] In one embodiment, the grooves are arranged at intervals along the width direction of the pole piece; and the gap between any two of the grooves is 30 μm-300 μm.

[0008] In one embodiment, the width of the groove is ≤30 μm.

[0009] In one embodiment, the depth of the groove is ≤60 μm.

[0010] In one embodiment, the total area of ​​the grooves accounts for 10%-30% of the area on the pole piece.

[0011] In one embodiment, the groove extends from a surface of the inorganic particle layer away from the current collector toward the active material layer, and the groove penetrates the inorganic particle layer and at least a portion of the active material layer.

[0012] In one embodiment, the peel strength between the inorganic particle layer and the active material layer is ≥10 N / m.

[0013] In one embodiment, the thickness of the inorganic particle layer is 30nm-100nm.

[0014] In one embodiment, the porosity of the inorganic particle layer is 30%-60%.

[0015] In one embodiment, the surface density of the inorganic particle layer is 4×10 -6 g / cm 2 -1×10 -5 g / cm 2 .

[0016] In one embodiment, the inorganic particles of the inorganic particle layer are any one of aluminum oxide, silicon dioxide, silicon nitride, zirconium oxide, boron nitride, titanium dioxide and zinc oxide.

[0017] In one embodiment, the thickness of the active material layer is 150 μm-450 μm.

[0018] In one embodiment, the surface density of the active material layer is 0.02 g / cm 2 -0.06g / cm 2 .

[0019] A second aspect of the utility model provides a battery, comprising the pole piece described in the first aspect.

[0020] The utility model adopts the above technical solution to achieve the following beneficial effects:

[0021] (1) The pole piece provided by the utility model is a thick-coated pole piece, the thickness of the active material layer coated on the current collector is large, and the battery energy density is large.

[0022] (2) The electrode provided by the utility model comprises an inorganic particle layer, and the particle size of the inorganic particles in the inorganic particle layer is 10nm-50nm, which is beneficial to improving the fast charging performance of the battery.

[0023] (3) The inorganic particle layer and the active material layer provided by the utility model are provided with grooves on their surfaces, which can reduce the tortuosity of lithium ion transmission inside the electrode and improve the charging performance of the battery.

[0024] (4) The inorganic particle layer and the active material layer provided by the utility model have a strong bonding force, which is beneficial to improving the energy density of the battery.

[0025] (5) The inorganic particle layer provided by the utility model can not only increase the safety performance of the battery, but also isolate the positive and negative electrodes, which is beneficial to further improve the energy density of the battery.

[0026] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Shown is a schematic diagram of the electrode processing process in Example 1.

[0028] Figure 2 Shown is a top view of a pole piece with grooves etched into it.

[0029] Figure 3 Shown is a microscopic schematic diagram of the inorganic particle layer.

[0030] Description of Figure Numbers:

[0031] 11. Active material layer; 12. Inorganic particle layer; 13. Groove; Y is the width direction of the electrode; W is the width of the groove. DETAILED DESCRIPTION

[0032] The specific implementation of the present invention is described in detail below. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0033] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention relates.

[0034] The first aspect of the utility model provides a pole piece, the pole piece comprising:

[0035] A current collector, an active material layer arranged on the surface of the current collector, and an inorganic particle layer arranged on the surface of the active material layer away from the current collector, wherein the particle size of the inorganic particles in the inorganic particle layer is 10nm-50nm; grooves are arranged on the inorganic particle layer and the active material layer. The utility model arranges an active material layer and an inorganic particle layer on the current collector, and the thickness of the active material layer is relatively thick so that the battery has a higher energy density, but when the thickness is relatively thick, the charging performance of the battery will be reduced. Therefore, by arranging grooves on the inorganic particle layer and the active material layer, the tortuosity of lithium ion transmission inside the pole piece is reduced, thereby improving the charging performance of the battery. The active material layer is vulnerable to damage during the formation of the grooves, and the inorganic particle layer can protect the active material layer during the formation of the grooves, thereby improving the energy density of the battery.

[0036] In the utility model, an active material layer is arranged on the current collector.

[0037] In some embodiments, the thickness of the active material layer is 150 μm-450 μm, for example, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm and 450 μm. The thickness of the active material layer refers to the thickness of the active material layer coated on the surface of the current collector.

[0038] In some embodiments, the pole piece is a thick-coated pole piece, that is, the thickness of the active material layer on the surface of the current collector is relatively thick, which is beneficial to improving the energy density of the battery.

[0039] In some embodiments, the surface density of the active material layer is 0.02 g / cm 2 -0.06g / cm 2 , for example, it can be 0.02 g / cm 2 , 0.03g / cm 2 , 0.04g / cm 2 , 0.05g / cm 2 and 0.06g / cm 2 The surface density of the active material layer is the surface density where no grooves are provided.

[0040] The test method of the surface density in the utility model is to use an analytical balance to weigh the current collector foil and the pole piece containing the active material layer but not the inorganic particle layer of the same area size S, the weight of the foil is recorded as m1, the weight of the pole piece is recorded as m2, and finally the single-sided surface density (m2-m1) / 2S is obtained and recorded as the surface density. The test method of the thickness is to measure the thickness of the pole piece by a spiral micrometer.

[0041] The active material in the active material layer of the positive electrode in the present invention is not specifically limited, and may be any one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium titanate, lithium cobaltate, and lithium manganate.

[0042] The active material in the active material layer of the negative electrode sheet of the present invention is not particularly limited, and may be, for example, a carbon-based material or a silicon-based material.

[0043] In the present invention, an inorganic particle layer is disposed on the surface of the active material layer. The inorganic particle layer deposited on the surface of the active material layer can protect the active material layer, and the inorganic particle layer can also isolate the positive and negative electrodes, which is beneficial to further improve the energy density of the thick-coated electrode battery.

[0044] The particle size of the inorganic particles in the inorganic particle layer described in the utility model is 10nm-50nm, for example, it can be 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm and 50nm, which can be obtained by atomic deposition. When the particle size of the inorganic particles is 10nm-50nm, it is beneficial to improve the battery's charging performance and energy density. The particle size of the inorganic particles is an average particle size, and the testing method is to stick the sample on a conductive adhesive, use a scanning electron microscope or a transmission electron microscope to observe the morphology of the particles, and mark the size of the particles. Figure 3 Shown is a microscopic schematic diagram of the inorganic particle layer.

[0045] In some embodiments, the conditions of the atomic deposition are not particularly limited, for example, the deposition temperature is 100° C.-300° C., and the deposition time is 10 s-45 s.

[0046] In some embodiments, the thickness of the inorganic particle layer is 30nm-100nm, for example, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm and 100nm. Preferably, the thickness of the inorganic particle layer is 60nm-80nm.

[0047] In some embodiments, the porosity of the inorganic particle layer is 30%-60%, for example, 30%, 40%, 45%, 50%, 55% and 60%. There are pores between the deposited inorganic particles, which is conducive to the transmission of ions, thereby improving the conductivity of the battery. The porosity test method in the utility model can be measured using instruments and methods known in the art. For example, the pole piece samples are cut into the same size, and the porosity tester is used to test them in turn, and finally the average porosity of the pole piece samples is obtained, and the test is performed with reference to the national standard GB / T 24586-2009.

[0048] In some embodiments, the surface density of the inorganic particle layer is 4×10 -6 g / cm2 -1×10 -5 g / cm 2 , for example, it can be 4×10 -6 g / cm 2 , 6×10 -6 g / cm 2 , 8×10 -6 g / cm 2 and 1×10 -5 g / cm 2 The surface density of the inorganic particle layer is the surface density where no grooves are provided.

[0049] In some embodiments, the inorganic particles in the inorganic particle layer are any one of aluminum oxide, silicon dioxide, silicon nitride, zirconium oxide, boron nitride, titanium dioxide and zinc oxide.

[0050] In some embodiments, when the inorganic particles of the inorganic particle layer are aluminum oxide, the deposition raw material may be at least one of triethylaluminum (CH3CH2)3Al, trimethylaluminum, aluminum triacetylacetonate and aluminum trichloride, and the deposition raw material reacts with the hydroxyl group in the active material layer during the atomic deposition process to generate aluminum oxide. The atomically deposited inorganic particles are irregularly arranged on the surface of the active material layer, and a large number of pores for ion transmission are formed between the particles, which is beneficial to improve the fast charging capability of the battery.

[0051] In some embodiments, the peel strength between the inorganic particle layer and the active material layer is ≥10N / m. The test method for peel strength described in the present invention is tested according to the national standard GB / T 2792-2014. The peel strength between the inorganic particle layer and the active material layer in the present invention is ≥10N / m by atomically depositing inorganic particles on the surface of the active material layer. At this time, the thickness of the inorganic particle layer is very thin, and when the inorganic particles are triethylaluminum (CH3CH2)3Al, during the atomic deposition process, triethylaluminum can react with the hydroxyl group in the active material layer, thereby improving the bonding force between the active material layer and the inorganic particle layer.

[0052] The inorganic particle layer and the active material layer are provided with grooves, which are beneficial to reducing the lithium / sodium ion transmission path, increasing the lithium / sodium ion energy density and enhancing the fast charging capability of the lithium / sodium ion battery.

[0053] In some embodiments, the groove extends from a surface of the inorganic oxide facing away from the current collector toward the active material layer, and the groove penetrates the inorganic particle layer and at least a portion of the active material layer.

[0054] In some embodiments, the groove is in the shape of a strip.

[0055] In some embodiments, the cross-section of the groove is triangular, trapezoidal or rectangular.

[0056] In some embodiments, the grooves are arranged at intervals along the width direction of the pole piece, for example Figure 2 As shown in Y; and the gap between any two of the grooves is 30μm-300μm, for example, it can be 30μm, 50μm, 80μm, 100μm, 150μm, 200μm, 250μm and 300μm.

[0057] In some embodiments, the width of the groove is ≤30 μm, for example, 30 μm, 20 μm, 10 μm, 5 μm and 1 μm. The width of the groove in the present invention refers to the maximum width of the groove, for example Figure 2 As shown in W.

[0058] In some embodiments, the depth of the groove is ≤60 μm, for example, it may be 60 μm, 50 μm, 40 μm, 30 μm, 20 μm, 10 μm, or 1 μm.

[0059] In some embodiments, the total area of ​​the grooves accounts for 10%-30% of the area on the pole piece, for example, 10%, 15%, 20%, 25% and 30%. The total area of ​​the grooves accounts for the area on the pole piece refers to the ratio of the projected area of ​​all the grooves on the pole piece to the total area of ​​the pole piece.

[0060] In some embodiments, the trench is obtained by etching.

[0061] In some embodiments, the etching method is laser etching, which uses laser to etch the inorganic particle layer and the active material layer to create defects on the surfaces of both layers, reduce the tortuosity of ion transmission, and help improve the battery dynamics performance.

[0062] In some embodiments, the laser etching conditions include: pulse energy of 1 μJ-7 μJ, laser power of 1 W-6 W, laser scanning speed of 5 mm / s-45 mm / s, and etching time of 1 s-5 s. The etching time is the time of a single etching.

[0063] In the utility model, the inorganic particle layer can prevent the molten beads foreign matter sputtered during laser etching from damaging the active material layer, thereby facilitating improving the energy density of the battery.

[0064] In some embodiments, the pole piece further includes molten beads located on the surface of the inorganic particle layer.

[0065] In some embodiments, the distribution area of ​​the molten bead foreign matter accounts for 2%-15% of the pole piece area.

[0066] A second aspect of the utility model provides a battery, comprising the pole piece described in the first aspect.

[0067] The positive and negative electrode sheets and the separator described in the first aspect are stacked or wound and then injected with electrolyte to obtain a battery.

[0068] In some embodiments, the positive and negative electrode sheets described in the first aspect are stacked or wound and then injected with electrolyte to obtain a diaphragm-free battery. Since there is an inorganic particle layer between the positive and negative electrode sheets of the battery, which is an insulating layer and there are gaps between the inorganic particles for ions to pass through, the electrode sheet composed of the first aspect can avoid the use of a diaphragm, reduce the mass of the battery, and improve the mass energy density of the battery.

[0069] In this embodiment, the material of the electrolyte is not specifically limited.

[0070] The following will be combined with the embodiments of the utility model to clearly and completely describe the technical solutions in the embodiments of the utility model. Obviously, the described embodiments are only part of the embodiments of the utility model, not all of the embodiments. Based on the embodiments of the utility model, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the utility model.

[0071] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0072] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand rather than limit the present invention.

[0073] Example 1

[0074] (1) Preparation of positive and negative electrodes:

[0075] Preparation of positive electrode sheet: The ternary material, binder polyvinylidene fluoride (PVDF), and conductive agent conductive carbon black (SP) are mixed in a mass ratio of 8:1:1, and then fully stirred in N-methylpyrrolidone (NMP) to obtain the corresponding positive electrode slurry. The positive electrode slurry is coated on the front and back sides of the aluminum foil, dried, and pressed to obtain a positive electrode sheet preform, which has a thickness of 287 μm and a surface density of 0.047 g / cm 2 positive electrode active material layer.

[0076] Preparation of negative electrode sheet: Graphite, binder and conductive agent SP were mixed in a mass ratio of 8:1:1, and then stirred in deionized water to obtain the corresponding negative electrode slurry; the negative electrode slurry was coated on the front and back sides of the copper foil, and dried and pressed to obtain a negative electrode sheet preform, which had a thickness of 360 μm and a surface density of 0.028 g / cm 2 of the negative electrode active material layer.

[0077] like Figure 1 As shown, inorganic particles are deposited on the surface of the active material layer 11 by atomic deposition to obtain an inorganic particle layer 12. Specifically, the pre-prepared positive electrode sheet preform and negative electrode sheet preform obtained above are placed in an atomic deposition device, and triethylaluminum (CH3CH2)3Al is used for atomic deposition at 200°C for 30s to obtain an aluminum oxide layer, that is, a pole sheet including an inorganic particle layer is obtained. The particle size of the aluminum oxide particles is about 30nm, the thickness of the inorganic particle layer is 70nm, and the porosity of the inorganic particle layer is 50%.

[0078] like Figure 1 As shown, the inorganic particle layer 12 and the active material layer 11 obtained above are etched to obtain a pole piece containing grooves 13. The laser etching uses ultrashort intense laser pulses, the pulse energy is 3.8 μJ, the laser power is 4 W, the laser scanning speed is 25 mm / s, and the single etching time is 2 s. The width of the groove is 15 μm, the depth of the groove is 30 μm, the total area of ​​the groove accounts for 20% of the area on the pole piece, the gap between any two grooves is 200 μm, and the surface density of the inorganic particle layer is 5×10 -6 g / cm 2 .

[0079] (2) Assembly of lithium batteries:

[0080] Preparation of electrolyte: Ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0081] The processed negative electrode sheet and the processed positive electrode sheet are stacked on each other to obtain a battery cell, and the battery cell is filled with aluminum plastic film, dried, injected with electrolyte, packaged, formed, and divided into different capacities to obtain a lithium-ion battery.

[0082] Example 2

[0083] This example is used to illustrate the effect of the thickness of the inorganic particle layer on the performance of the electrode.

[0084] Example 2-1

[0085] The operation was carried out in accordance with the method described in Example 1, except that the time of atomic deposition was changed so that the thickness of the inorganic particle layer was about 40 nm.

[0086] Example 2-2

[0087] The operation was carried out in accordance with the method described in Example 1, except that the time of atomic deposition was changed so that the thickness of the inorganic particle layer was about 90 nm.

[0088] Example 3

[0089] This example is used to illustrate the influence of the surface density and porosity of the inorganic particle layer on the performance of the electrode.

[0090] Example 3-1

[0091] The operation was carried out in accordance with the method described in Example 1, except that the temperature of the atomic deposition was 150° C. and the porosity of the inorganic particle layer was 40%.

[0092] Example 3-2

[0093] The operation was carried out in accordance with the method described in Example 1, except that the temperature of the atomic deposition was 250° C. and the porosity of the inorganic particle layer was 60%.

[0094] Example 4

[0095] This embodiment is used to illustrate the influence of the etched grooves on the performance of the pole piece.

[0096] Example 4-1

[0097] The operation was carried out in accordance with the method described in Example 1, except that the power of the laser etching was changed to 2 W, the pulse energy of the laser etching was 1 μJ, the depth of the groove was 15 μm, and the width of the groove was 8 μm.

[0098] Example 4-2

[0099] The operation was carried out in accordance with the method described in Example 1, except that the power of the laser etching was changed to 6 W, the pulse energy of the laser etching was 6 μJ, the depth of the groove was 56 μm, and the width of the groove was 27 μm.

[0100] Example 4-3

[0101] The operation was carried out in accordance with the method described in Example 1, except that the gap of the control groove was 50 μm.

[0102] Example 4-4

[0103] The operation was carried out in accordance with the method described in Example 1, except that the gap of the control groove was 280 μm.

[0104] Comparative Example 1

[0105] This comparative example is used to illustrate the preparation of a pole piece when no inorganic particle layer and grooves are provided on the active material layer.

[0106] The operation is carried out in accordance with the method described in Example 1, except that no inorganic particle layer is deposited on the active material layer, and the active material layer is not etched.

[0107] Comparative Example 2

[0108] This comparative example is used to illustrate the preparation of a pole piece when etching is performed without providing an inorganic particle layer on the active material layer.

[0109] The operation was carried out in accordance with the method described in Example 1, except that no inorganic particle layer was deposited on the active material layer, but the active material layer was laser etched.

[0110] During the laser etching process, molten beads are generated, which are splashed onto the surface of the active material layer and cause damage to the active material layer. The distribution area of ​​the molten beads accounts for about 10% of the electrode area.

[0111] Comparative Example 3

[0112] This comparative example is used to illustrate that an inorganic particle layer is provided on the active material layer, but the inorganic particle layer is not atomically deposited on the surface of the active material layer.

[0113] According to the method described in Example 1, an inorganic particle layer is provided on the active material layer, and the active material layer and the inorganic particle layer are laser etched. The difference is that the inorganic particle layer is provided by coating commercially available aluminum oxide particles with a particle size of 300nm onto the surface of the active material layer, and the thickness of the inorganic oxide layer is 1μm.

[0114] Comparative Example 4

[0115] This comparative example is used to illustrate the preparation of a pole piece when an inorganic particle layer is provided on an active material layer but etching is not performed.

[0116] The inorganic particle layer is deposited on the active material layer according to the method described in Example 1, except that the active material layer and the inorganic particle layer are not etched.

[0117] Test Case

[0118] The batteries obtained in the examples and comparative examples were tested for the first time for coulombic efficiency, energy density and 2C capacity retention rate. The experimental results are shown in Table 1.

[0119] (1) First efficiency test method: After the battery is manufactured, it is first charged to 3.75V at a constant current of 0.1C to obtain the formation capacity C0. Then the battery is divided into different capacities, charged to 4.25V at a constant current of 0.33C, and then charged to I≤0.05C at a constant voltage of 4.25V to obtain the battery capacity C1 after the capacity division. After standing for 5 minutes, the battery is discharged to 2.8V at a constant current of 1C to obtain the discharge capacity C2, and then discharged to 2.8V at a constant current of 0.1C to obtain the discharge capacity C3, and then discharged to 2.8V at a constant current of 0.01C to obtain the discharge capacity C4; the first coulomb efficiency (first efficiency) is calculated according to (C2+C3+C4) / (C0+C1)*100%.

[0120] (2) Energy density test method: First, weigh each group of tested batteries and record the mass of the battery as m. Then, at 25°C, charge the battery at a constant current of 0.1C to 4.25V, then charge at a constant voltage of 4.25V to a current ≤0.05C. After standing for 5 minutes, discharge at a constant current of 0.1C to 2.8V to obtain the discharge energy Q. The battery energy density is calculated as Q / m.

[0121] (3) 2C capacity retention rate test method: At 25°C, first charge the battery to 4.25V at a constant current of 0.33C, then charge at a constant voltage of 4.25V to a current of I≤0.05C, and record the battery's 0.33C charging capacity as C0. After standing for 5 minutes, discharge the battery to 2.8V at a constant current of 0.5C. After standing for 5 minutes, charge the battery to 4.25V at a constant current of 2C, then charge at a constant voltage of 4.25V to a current of I≤0.05C, and record the battery's 2C charging capacity as C1. The 2C charging capacity retention rate is calculated according to C1 / C0*100%.

[0122] (4) Liquid absorption rate test method: The laminated batteries prepared in the comparative example and the example are weighed and recorded as a. One battery from each group is placed in the electrolyte for 24 hours to fully absorb the electrolyte. After the electrolyte is absorbed, the battery is pressed for 2 to 3 minutes (to remove the electrolyte on the surface of the battery), and the weight is recorded as b. The liquid absorption rate of the battery is (ba) / a×100%.

[0123] Table 1

[0124]

[0125]

[0126] The battery composed of the pole pieces of the utility model has higher energy density, capacity retention rate and initial efficiency, and because the inorganic particle layer can play the role of isolating the positive and negative pole pieces, it is also beneficial to improve the energy density of the battery.

[0127] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0128] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A pole piece, characterized in that: The pole piece comprises: A current collector, an active material layer disposed on the surface of the current collector, and an inorganic particle layer disposed on the surface of the active material layer away from the current collector, wherein the particle size of the inorganic particles in the inorganic particle layer is 10nm-50nm; Grooves are arranged on the inorganic particle layer and the active material layer.

2. The pole piece according to claim 1, characterized in that: The grooves are arranged at intervals along the width direction of the pole piece; and the gap between any two of the grooves is 30 μm-300 μm.

3. The pole piece according to claim 1, characterized in that: The width of the groove is ≤30 μm; and / or, the depth of the groove is ≤60 μm; and / or, the total area of ​​the groove accounts for 10%-30% of the area on the pole piece.

4. The pole piece according to claim 1, characterized in that: The groove extends from a surface of the inorganic particle layer away from the current collector toward the active material layer, and the groove penetrates the inorganic particle layer and at least a portion of the active material layer.

5. The pole piece according to claim 1, characterized in that: The peeling strength between the inorganic particle layer and the active material layer is ≥10N / m.

6. The pole piece according to claim 1, characterized in that: The thickness of the inorganic particle layer is 30nm-100nm.

7. The pole piece according to claim 1, characterized in that: The porosity of the inorganic particle layer is 30%-60%; and / or, The surface density of the inorganic particle layer is 4×10 -6 g / cm 2 -1×10 -5 g / cm 2 .

8. The pole piece according to claim 1, characterized in that: The inorganic particles in the inorganic particle layer are any one of aluminum oxide, silicon dioxide, silicon nitride, zirconium oxide, boron nitride, titanium dioxide and zinc oxide.

9. The pole piece according to claim 1, characterized in that: The thickness of the active material layer is 150 μm-450 μm; and / or, The surface density of the active material layer is 0.02 g / cm 2 -0.06g / cm 2 .

10. A battery, characterized in that: A pole piece comprising any one of claims 1 to 9.